Characteristics of the electromagnetic environment created by radiations of user equipment of ...4G/5G/6G cellular (mobile) communications in buildings - V. I. Mordachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The goal of the work is to substantiate the technique for assessing the intensity of electromagnetic background generated by the set of radiating user devices of mobile communications in multi-storey buildings. For known empirical models of radio wave propagation in buildings, expressions are obtained for the probability distribution density and expectation of the power flux density of electromagnetic fields generated inside building by these sources from various parts of the building's interior space: from the near zone with radio wave propagation conditions similar to free space; and from the far zone, for which, along with intense attenuation of radio waves due to internal obstacles, a «quasi-waveguide» propagation of radio waves along corridors and industrial premises is also possible in certain directions. Relationships are obtained for the average levels of individual components of the electromagnetic background, determined as scalar sums of power flux density values of the fields generated by the sets of radiating devices of both the near zone and the far zone as a whole or its individual parts, characterized by different conditions of radio wave propagation. A method is proposed for assessing the electromagnetic background inside buildings based on approximation of sections of the inner surface of the premises in which the observation point is located, and the outer surface of the building, in the inner space of which radiation sources are randomly distributed, by the corresponding sections of the inner and outer spherical surfaces that are the subtend areas of the corresponding solid angles, in space elements of which a different spatial densities and radiation powers of sources and different conditions of radio wave propagation are possible. The results can be used to analyze the electromagnetic ecology of habitat and the electromagnetic safety of population at the full-scale implementation of 4G/5G/6G mobile communications, as well as to analyze the electromagnetic compatibility of systems using frequency bands for mobile communications on a primary and secondary basis.